PROSES KONSENSUS DALAM RELOKASI HUNIAN KORBAN ERUPSI GUNUNG MERAPI 2010 DAN FAKTOR YANG MEMPENGARUHI STUDI KASUS DUSUN PELEMSARI DAN DUSUN PANGUKREJO, DESA UMBULHARJO, KECAMATAN CANGKRINGAN, KABUPATEN SLEMAN - , Bagus Ramadhan; , Prof. Ir. Bakti Setiawan, MA., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Merapi 2010 eruption cause huge loss, some hamlet located in slope of Merapi mountain swap by eruption materials of Merapi. In Cangkringan District, 2271 houses damaged. After the eruption, Sleman Regency government made a policy to relocate 9 hamlets because itâs located in direct impact area of Merapi 2010 eruption. This policy choosen because damaged level in that hamlets and relocate inhabitant to safer place to live. Two of those hamlets are Pelemsari Hamlet and Pangukrejo Hamlet in Umbulharjo Village. But at that time, inhabitant stil objected because land status problem in their origin hamlet which they still willing to posses. This research aim to describe consensus process between government and community within housing relocation in Pelemsari Hamlet and Pangukrejo Hamlet, Umbulharjo Village, Cangkringan District, Sleman Regency. Its describe the dynamic in the community so that consensus can reached or not. Beside itâs also identify factors that influence consensus process. This research found that consensus process which happen in both hamlets are negotiation process. Government and community bargaining their interest. Negotiation process of both hamlets can be devide into three phase, first pre negotiation phase, second is negotiation phase and third is post negotiation phase which Pelemsari Hamlet can relocate all of their inhabitant while Pangukrejo Hamlet only 25 HH. Factors that mostly affect negotiation process is house damage level because relocation decision based on how much damaged happen to the house. And another factors are community representation, setting agenda before negotiation process, land and land guarantee.